The ownership and management of housing in the new towns: report submitted to the Minister of Housing and Local Government by J B Cullingworth and V A Karn - Great Britain. Ministry of Housing and Local Government; Cullingworth, J. B.; Karn, Valerie Ann (London : Her Majesty's Stationery Office, 1968)
36